2017
DOI: 10.1007/s10103-017-2367-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture-induced analgesic effect and molecular alterations in an incision pain model: a comparison with electroacupuncture-induced effects

Abstract: Low-level laser acupuncture (LLLA) produces photobiomodulation through acupuncture point and is an alternative to low-level laser therapy. Although the analgesic effect of LLLA on chronic pain has been proven, its effect on acute postincisional pain has yet to be investigated. A plantar incision (PI) model was used to mimic human postsurgical pain. Male adult rats received GaAlAs laser irradiation at the right ST36 acupoint immediately after operation and on the following 4 days. Three laser treatment groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…The ST36 acupoint is located on the tibialis anterior muscle of the leg, and its functions in traditional oriental medicine are to fortify the spleen and stomach, replenish qi and nourish blood, clear and activate meridians, and nourish the channels [ 15 ]. Lots of pre-clinical works indicated that stimulations applied on this acupoint (e.g., BVA, electro-acupuncture, laser-acupuncture, or moxibustion) can produce significant pain-relieving effects under diverse conditions, such as neuropathic, incision, or inflammatory pain state [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ST36 acupoint is located on the tibialis anterior muscle of the leg, and its functions in traditional oriental medicine are to fortify the spleen and stomach, replenish qi and nourish blood, clear and activate meridians, and nourish the channels [ 15 ]. Lots of pre-clinical works indicated that stimulations applied on this acupoint (e.g., BVA, electro-acupuncture, laser-acupuncture, or moxibustion) can produce significant pain-relieving effects under diverse conditions, such as neuropathic, incision, or inflammatory pain state [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all LA treatments attenuated post-PI tactile allodynia in the ipsilateral paw. LA is effective in alleviating pain and some pain relief mechanisms caused by LA were discovered [16]. From many scientific reports and our studies, PBMT is an easy to use alternative medicine with a high potential to treat chronic diseases.The formula, based on traditional Chinese medicine, should be better defined using clinical trials.…”
Section: Resultsmentioning
confidence: 95%
“…However, such a paradigm has slowly shifted in the last decade with the acknowledgment that problems with study design, a powerful placebo effect from sham intervention, and insufficient treatment groups commonly contribute to the contradicting results in the literature. With the emerging availability of better‐designed studies utilizing factorial experiments, or pragmatic or cluster randomized clinical trials to present a more rigorous discussion addressing the multi‐factorial and complexity of acupuncture, 40–42 more evidence suggests that different styles of acupuncture, for example, laser acupuncture, ultrasound acupuncture, electroacupuncture, and sham acupuncture induce different bioeffects on pain modulation 43–46 . For example, alterations of objective measures of blood flow volume and skin temperature in the fingers and toes were observed after ultrasound acupuncture in healthy participants 47 .…”
Section: Discussionmentioning
confidence: 99%